PEMBUATAN VIDEO DOKUMENTER FENOMENA ROKOK - Tommy Karyadi; Fitri Dwi Kartikasari; Hendra Dinata (Perpustakaan Universitas Surabaya, 2018)
Electric cigarettes are now growing in the community. This stuff is considered an alternative for people who want to stop using regular cigarettes. Though the users of electric cigarette not yet know about information of electric cigarette. With the problem, there was a documentary video about the phenomenon of electric cigarettes for people to know information about everything of electric cigarette. This documentary video was created using Adobe Premiere CC5 and the results can be accessed through a link from the promotional media in the form of games. For some parts of the video edited using software Adobe After Effect CC5. This documentary video has passed the trial and evaluation process by showing the video and giving questionnaires to 20 people who are aged above 16 years. Responses obtained quite well because the information provided can be understood so that it can deliver the video messages informatively.